PENGARUH KEPEMIMPINAN TRANSFORMASIONAL & TRANSAKSIONAL, SERTA KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL PADA KARYAWAN PT. BAHANA PRESTASI - Nehemya Nehemya (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: This research aims to know the influence of transformational leadership, transactional leadership and job satisfaction to organizational commitment. The location for this research is PT. Bahana Prestasi that located in Cileungsi, Cibitung and Jakarta.This research was done to 124 respondents by using quantitive-descriptive approach. Thus, data analysis which is used is statiscic analysis in the form of doublelinear regression test. The result of this research shows that eiter simultaneously orpartially, the variabel of transformational leadership, transactional leadership and job satisfaction influence organizational commitment of the employee of PT. Bahana Prestasi. It has been proven from the result of (f) simultan test which shows confer (40,640) with significant point (0.000) which is much smaller than alpha 0.05. Alongwith the result of (t) partial shows significant point of three independent variables succesion as big as 0.01, 0.06 and 0.001 which is smaller than alpha 0.05. Therefore, the accepted asumption is H0 rejected.Keywords: transformational leadership, transactional leadership, job satisfaction, organizational commitment